Firm Competitive Strategies and the Likelihood of Survival. The Spanish Case - Raquel Ortega-Argilés; Rosina Moreno (Max Planck Institute of Economics, 2007)
This paper analyses the impact that some managerial competitive strategies followed by a firm may have on its survival. We have not only considered the classic strategies related to the passive learning process defined by Jovanovic (e.g., R&D or advertisement expenses), but we have also taken into account the active learning process ideas given by Ericson and Pakes. This way, we study the effect of product and process innovative strategies, with a detailed desegregation of their functions, on firmâs survival likelihood. Several non-parametric, semi-parametric and parametric techniques are computed to check the effect of the active learning theory on business survival in a set of Spanish manufacturing firms (1990-2001).
Keywords: L11; M13; O31; 330; firm survival; active learning theory; duration analysis.; Unternehmensentwicklung; Wettbewerbsstrategie; Lernprozess; Verarbeitendes Gewerbe; Spanien